Simulating the effects of short-term synaptic plasticity on postsynaptic dynamics in the globus pallidus - Brody, Moran; Korngreen, Alon (Frontiers in Systems Neuroscience, 2013)
The rat globus pallidus (GP) is one of the nuclei of the basal ganglia and plays an important role in a variety of motor and cognitive processes. In vivo studies have shown that repetitive stimulation evokes complex modulations of GP activity. In vitro and computational studies have suggested that short-term synaptic plasticity (STP) could be one of the underlying mechanisms. The current study used simplified single compartment modeling to explore the possible effect of STP on the activity of GP neurons during low and high frequency stimulation. To do this we constructed a model of a GP neuron connected to a small network of neurons from the three major input sources to GP neurons: striatum (Str), subthalamic nucleus (STN) and GP collaterals. All synapses were implemented with a kinetic model of STP. The in vitro recordings of responses to low frequency repetitive stimulation were highly reconstructed, including rate changes and locking to the stimulus. Mainly involved were fast forms of plasticity which have been found at these synapses. . The simulations were qualitatively compared to a data set previously recorded in vitro in our lab. Reconstructions of experimental responses to high frequency stimulation required adding slower forms of plasticity to the STN and GP collateral synapses, as well as adding metabotropic receptors to the STN-GP synapses. These finding suggest the existence of as yet unreported slower short-term dynamics in the GP. The computational model made additional predictions about GP activity during low and high frequency stimulation that may further our understanding of the mechanisms underlying repetative stimulation of the GP.